2021
DOI: 10.26855/ijfsa.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Peri-Urban Agriculture on the Fringes of the Metropolis of Rabat, Morocco

Abstract: The current study was aimed to assess practices, roles and challenges of peri-urban agriculture in Rabat Metropolis. Through purposive and stratified random sampling methods 50 respondents were selected. To achieve the objectives of this study, both qualitative and quantitative methods of data analysis were used. Data collection from farmers was based on field observation, interviews and field surveys. Descriptive statistics such as frequency distribution, Chi-square test, tests of normality and homogeneity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study also revealed a strong dependence of visited farms on chemical inputs and fuels, and an absence of sustainable production techniques such as direct seeding. Nevertheless, the region is characterized by diversified polyculturelivestock agro-systems (Hakimi and Brech, 2021). The exorbitant prices of inputs have prevented many farmers from providing them, but this has indirectly influenced the level of agro-ecological sustainability, which recorded a slightly high score of 38.1 (Table 2).…”
Section: Analysis Of the Three Scales Of Sustainability Agro-environm...mentioning
confidence: 99%
“…The study also revealed a strong dependence of visited farms on chemical inputs and fuels, and an absence of sustainable production techniques such as direct seeding. Nevertheless, the region is characterized by diversified polyculturelivestock agro-systems (Hakimi and Brech, 2021). The exorbitant prices of inputs have prevented many farmers from providing them, but this has indirectly influenced the level of agro-ecological sustainability, which recorded a slightly high score of 38.1 (Table 2).…”
Section: Analysis Of the Three Scales Of Sustainability Agro-environm...mentioning
confidence: 99%